PENGARUH PENGEMBANGAN KARIR MOTIVASI KERJA DAN KESELAMATAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KARYAWAN DI PT. TIRTAKENCANA - Muhammad Alfaizi; Veny Puspita; M Noor Armi (Bisnis-Net, 2023)
study aims determine how muchinfluence career development, workmotivation and occupational health safety have onemployee productivity PT. Tirtakencana. population study were 35 employees. sample research 35 permanent employees. In this study sampling technique used total sampling technique, the method of analysis of research was a quantitative method using multiplelinear regressionanalysis tools, multiple correlation, determination, t test and f test which processed software, IBM SPSS 16 From research results can concluded partially, career development an effect employee productivity, work motivation has significantnegative effect on employeeproductivity and occupational health safety has effect on employeeproductivity, simultaneously careerdevelopment, workmotivation and occupational healthsafety have an effect on employeeproductivity at PT, Tirtakencana.Keywords: Career Development, Work Motivation, Occupational Health Safety, And Employee Productivity